Knee extension strength profile of elite Greek soccer players - Tsiokanos, A.; Paschalis, V.; Valasotiris, K. (Isokinetics and Exercise Science, 2016)
BACKGROUND: The movements that soccer players have to perform during a game depend on lower limb muscles strength and clearly players with higher strength levels are able to perform better turning, sprinting and changing pace. The movements that soccer players have to perform during a game depend on lower limb muscles strength and clearly players with higher strength levels are able to perform better turning, sprinting and changing pace. OBJECTIVE: To compare the isokinetic peak torque of the knee extensors in a large number of elite Greek soccer players in relation to their position on the playing field. To compare the isokinetic peak torque of the knee extensors in a large number of elite Greek soccer players in relation to their position on the playing field. METHODS: Two-hundred and seventy-five soccer players: goalkeepers (n= 24), fullbacks (n= 67), center backs (n= 59), midfield players (n= 76) and forwards (n= 49) from the first division in Greece participated in this study. All participants performed an isokinetic test of the knee extensors at 30, 60 and 180°/s. Two-hundred and seventy-five soccer players: goalkeepers (n= 24), fullbacks (n= 67), center backs (n= 59), midfield players (n= 76) and forwards (n= 49) from the first division in Greece participated in this study. All participants performed an isokinetic test of the knee extensors at 30, 60 and 180°/s. RESULTS: In terms of knee extension strength the goalkeepers were the strongest while the fullbacks were the weakest players but strength normalization resulted in uniform knee extension strength irrespective of field position. In terms of knee extension strength the goalkeepers were the strongest while the fullbacks were the weakest players but strength normalization resulted in uniform knee extension strength irrespective of field position. CONCLUTIONS: The present findings provide a reference system for knee extension strength in soccer players. The present findings provide a reference system for knee extension strength in soccer players.